1998
DOI: 10.1136/oem.55.3.188
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of sick building syndrome and its associated risk factors in Singapore.

Abstract: Objectives-To investigate the occurrence of sick building syndrome in a tropical city, and its relation to indoor air quality and other factors. Methods-2856 oYce workers in 56 randomly selected public and private sector buildings were surveyed. The study consisted of a self administered questionnaire assessing symptoms and perception of the physical and psychosocial environment, inspection of the building plans and premises, and measurement of temperature, relative humidity, respirable particles, chemicals, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
63
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 11 publications
11
63
2
Order By: Relevance
“…The score of the SBS had been done according to the positive response, if one symptom recorded nearly every day, the mark given to the SBS scale. If two symptoms reported every day, two score were given and so on (Ooi et al, 1998). As showed in Table 4, number of respondents that had been categorized as having SBS using above criteria given, the Building A recorded 68.2% office workers having SBS compared to 25.9% of office workers in the Building.…”
Section: Prevalence Of Sick Building Syndrome (Sbs)mentioning
confidence: 99%
See 1 more Smart Citation
“…The score of the SBS had been done according to the positive response, if one symptom recorded nearly every day, the mark given to the SBS scale. If two symptoms reported every day, two score were given and so on (Ooi et al, 1998). As showed in Table 4, number of respondents that had been categorized as having SBS using above criteria given, the Building A recorded 68.2% office workers having SBS compared to 25.9% of office workers in the Building.…”
Section: Prevalence Of Sick Building Syndrome (Sbs)mentioning
confidence: 99%
“…Reported SBS symptoms were given to the respective respondents on each day of IAQ assessment conducted and the score given in the analysis of data commence. Based on the study by Ooi et al (1998), building occupants also must report symptoms occurrence of at least 1-3 days per week during four weeks past and the symptoms shown improvement when she/he away from work. Office workers will be defined as having SBS if they had at least one symptom of SBS symptoms and the symptoms appear at least once in a week.…”
Section: Socio-demographic Information Health Status and Prevalence mentioning
confidence: 99%
“…Other items (copy paper) and activities (photocopying and video terminal exposure) have been linked to symptoms (178). Other studies have suggested that shade, organic debris, landscaping quality, central electrostatic systems, ventilation rates, temperature, noise levels, dust control compliance, and patient gender may be important (23,42,77,215,264,298,308,344,437,440), as well as the presence of tobacco smoke (81,123,276). Psychosocial issues may be playing a role in building-related complaints.…”
Section: Indoor Air and Building-related Illnessmentioning
confidence: 99%
“…Norback et al (40) demonstrated that factors associated with SBS included smoking and psychosocial agents. Ooi et al (35) reported stress to be a significant and independent determinant of health complaints, and that in many cases, symptoms compatible with SBS were stress-related. These differences might be due to differences within the subject samples.…”
mentioning
confidence: 99%
“…With regards to amount of work, Ooi (1998) et al (35) reported that in individuals who daily worked eight hours or more, the SBS odds ratio (95% CI) was 1.47 (1.33-1.92). Mizoue (2001 AJEpi) et al (23) reported that exposure to environmental tobacco smoke and extensive overtime contribute to the development ofSBS symptoms.…”
mentioning
confidence: 99%